Targeting BRIX1 via Engineered Exosomes Induces Nucleolar Stress to Suppress Cancer Progression - Yu Gan; Qian Hao; Tao Han; Jing Tong; Qingya Yan; Hongguang Zhong; Bo Gao; Yanan Li; Zhisheng Xuan; Pengfei Li; Litong Yao; Yingying Xu; et al. (Advanced Science)
Abstract Elevated ribosome biogenesis correlates with the rapid growth and progression of cancer. Targeted blockade of ribosome biogenesis induces nucleolar stress, which preferentially leads to the elimination of malignant cells. In this study, it is reported that the nucleolar protein BRIX1 is a critical regulator for the homeostasis between ribosome biogenesis and p53 activation. BRIX1 facilitated the processing of pre‐rRNA by supporting the formation of the PeBoW complex. In addition, BRIX1 prevented p53 activation in response to nucleolar stress by impairing the interactions between MDM2 and the ribosomal proteins, RPL5, and RPL11, thereby triggering the resistance of cancer cells to chemotherapy. Conversely, depletion of BRIX1 induced nucleolar stress, which in turn activated p53 through RPL5 and RPL11, consequently inhibiting the growth of tumors. Moreover, engineered exosomes are developed, which are surface‐decorated with iRGD, a tumor‐homing peptide, and loaded with siRNAs specific to BRIX1, for the treatment of cancer. iRGD‐Exo‐siBRIX1 significantly suppressed the growth of colorectal cancer and enhanced the efficacy of 5‐FU chemotherapy in vivo. Overall, the study uncovers that BRIX1 functions as an oncoprotein to promote rRNA synthesis and dampen p53 activity, and also implies that targeted inhibition of BRIX1 via engineered exosomes can be a potent approach for cancer therapy.